Fasting substrate oxidation in relation to habitual dietary fat intake and insulin resistance in non-diabetic women: a case for metabolic flexibility? - Carstens Madelaine T; Goedecke Julia H; Dugas Lara; Evans Juliet; Kroff Jacolene; Levitt Naomi S; Lambert Estelle V (Nutrition & Metabolism, 2013)
Abstract Background Metabolic flexibility described as “the capacity of the body to match fuel oxidation to fuel availability” has been implicated in insulin resistance. We examined fasting substrate oxidation in relation to dietary macronutrient intake, and markers of insulin resistance in otherwise healthy women, with and without a family history of diabetes mellitus (FH DM). Methods We measured body composition (dual x-ray absorptiometry), visceral and subcutaneous adipose tissue area (VAT, SAT, using Computerised Tomography), fasting [glucose], [insulin], [free fatty acids], [blood lipids], insulin resistance (HOMA-IR), resting energy expenditure (REE), respiratory exchange ratio(RER) and self-reported physical activity in a convenience sample of 180 women (18-45 yrs). A food frequency questionnaire was used to assess energy intake (EI) and calculate the RER: Food Quotient (FQ) ratio. Only those with EI:REE (1.05 -2.28) were included (N=140). Insulin resistance was defined HOMA-IR (>1.95). Results The Insulin Resistant (IR) group had higher energy, carbohydrate and protein intakes (p < 0.05) and lower PA levels than Insulin Sensitive (IS) group (P < 0.001), but there were no differences in RER or RER:FQ between groups. However, nearly 50% of the variance in HOMA-IR was explained by age, body fat %, VAT, RER:FQ and FH DM (adjusted R2 = 0.50, p < 0.0001). Insulin-resistant women, and those with FH DM had a higher RER:FQ than their counterparts (p < 0.01), independent of body fat % or distribution. Conclusion In these apparently healthy, weight-stable women, insulin resistance and FH DM were associated with lower fat oxidation in relation to dietary fat intake, suggesting lower metabolic flexibility.